Corynebacterium riegelii sp. nov., an Unusual Species Isolated from Female Patients with Urinary Tract Infections - Funke, Guido (American Society for Microbiology, 1998)
Four strains of an unknown coryneform bacterium were isolated in pure culture from females with urinary tract infections. Strong urease activity and the ability to slowly ferment maltose but not glucose were the most significant phenotypic features of this catalase-positive, nonmotile, nonlipophilic, rod-shaped bacterium which served to distinguish it from all other presently defined coryneform bacteria. Chemotaxonomic investigations demonstrated that the unknown bacterium belonged to the genus Corynebacterium. Comparative 16S rRNA gene sequence analysis revealed that the isolates were genealogically identical and represented a new subline within the genus Corynebacterium, for which the designation Corynebacterium riegelii sp. nov. is proposed. The type strain of Corynebacterium riegelii is CCUG 38180 (DSM 44326, CIP 105310).